Pengaruh Keamanan, Kemudahan, Kepercayaan, Dan Risiko Kinerja Terhadap Keputusan Pembelian Secara Online: Studi Kasus Tokopedia.com di Kabupaten Lumajang - Setiawan, Edwin Hadi; Fauziah, Anisatul (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2017)
This study aims to determine how the influence of security, easy, trust and performance risk to online purchasing decisions either partially, simultaneously or dominant. This type of research using survey. The sample in this research 50 respondents there is users of tokopedia.com in Lumajang district. Methods of data collection with questionnaires distributed online using google forms. Data analysis using descriptive analysis and multiple regression analysis. The results showed variable security, easy, trust and performance risk partially have a significant positive effect on online purchasing decisions. While the simultaneous variable security, easy, trust and performance risk have a significant positive effect on online purchasing decisions. While the most dominant in influencing purchasing decision online is the security.